Preliminary Experience with Continuous Submucosal Anastomosis in Small-Diameter Hepaticojejunostomy during Single-Port Laparoscopic Choledochal Cyst Surgery in Children - Tang, Yingming; Zhang, Jie; Luo, Miao; Li, Fei; Huang, Huang; Zhou, Zhou; Fan, Xia; Qin, Zhijie; He, Guoqing; Zhuang, Yize (European Journal of Pediatric Surgery, 2023)
Purpose Hepaticojejunostomy anastomosis (HJA) is the most challenging aspect in single-port laparoscopic choledochal cystectomy and Roux-en-Y hepaticojejunostomy (SPCH) in children, especially in small-diameter anastomoses (diameters less than 5 mm), which are more susceptible to anastomotic stricture. We developed the continuous submucosal technique for HJA (CS-HJA) to lessen postoperative complications. The purpose of this study is to introduce our preliminary experiences with CS-HJA.Methods We retrospectively analyzed all available clinical data of children who underwent SPCH surgery between March 2020 and October 2022. We operated with CS-HJA on 10 children who were diagnosed with small-diameter hepaticojejunostomy (diameter less than 5 mm). Data collection mainly included demographic information, imaging data, perioperative details, and postoperative outcomes. Ten patients were included in this study. The average patient age was 55.2 months; the age range was 3 to 120 months, and the average weight was 11.6 kg; male–female ratio was 1:9. The choledocho had fusiform dilatation in five cases and cystic dilatation in five cases. There was no dilatation of the left and right hepatic ducts or intrahepatic bile ducts in all patients. All patients had no dilatation of the left and right hepatic ducts or intrahepatic bile ducts. All patients underwent a single-port laparoscopic bile-intestinal anastomosis using a submucosal jejunal anastomosis technique. Analysis of the duration of the bile-intestinal anastomosis, the length of the child's stay in the hospital after surgery, the intraoperative complications, and the postoperative complications was performed.Results All the 10 patients underwent successful SPCH by CS-HJA technique. The average length of time for hepaticojejunostomy ranged from 22 to 40 minutes, and the postoperative hospital stay was 5.2 to 9.2 days. There were no instances of bile leakage following the operation. At 17 to 30 months of follow-up, there was no abdominal pain or jaundice, and the reexamination of transaminases, bilirubin, and amylase were normal. Ultrasonography showed no bile duct stricture or dilated bile ducts, and the incision is elegant, and the families of the patients were satisfied.Conclusion In SPCH surgery in children, the CS-HJA technique is safe and feasible for small-diameter hepaticojejunostomy.
Keywords: continuous submucosal anastomosis; single-port laparoscopic surgery; choledochal cyst; hepaticojejunostomy